Analysis of Nutrition Care Chronic Renal Failure Patients with Health Technology Assessment (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Declined in nutritional status of hospitalized Chronic Renal Failure (CRF) patients were due to nutrient intake inadequate which required special attention from the Hospital Nutrition Service Team. This study analyzed the nutritional service on hospitalized CRF patients in Dr. Hasan Sadikin Hospital, Bandung using Health Technology Assessment. The study was conducted in 2014. The study design mixed method with concurrent embedded strategies. The hospital management, nutritionist and hospitalized CRF patients were qualitative subjects, selected using purposive sampling. Quantitative subjects selected using total sampling were 25 patients. Food weighing were used to measure food waste. The nutritional services technology aspects especially nutritional care using PAGT has not been entirely done. Nutritional monitoring and evaluation have not been well programmed and scheduled. The collaboration of nutritional care team have not been optimal. The food service mechanism are quite good while its portions are standardized yet. According to patient’s point of view towards food service quality, the food have less variety and taste. Total of cost damage from food waste are Rp.18.099,00 in a year. The lack of technological and organizational aspects can reduce the food service quality. According to the patient, the lack of food service quality will increase the food waste and total cost damage.